KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI KPK DAN FPB DI KELAS IV - Ika Nur Adhitya; Hamdani Hamdani; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the ability of elementary school students insolving mathematical problems on the least common multiple and thegreatest common divisor material. The indicators used in this study referto polya problem solving, namely understanding the problem, making aplan, executing the plan and checking again. This research method appliesdescriptive qualitative design. The subjects of this study were students ofclass IV B Elementary School 24 Southeast Pontianak. Sources of data inthis study consisted of the results of mathematical problem solving abilitytests and interview data. The results showed that students with a high levelof ability and students with a moderate level of ability were able to writewhat they knew well. The abilities possessed make it easy to apply problemsolving based on polya step, especially in understanding problems, makingplans and checking back. The difficulties experienced by students are inthe third stage, namely carrying out the plan, students often writeincomplete answers and have difficulty in arithmetic operations.Keywords: Math Problem Solving Ability, Least Common Multiple andThe Greatest Common Divisor Materials